2022
DOI: 10.3389/fncom.2021.760561
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Modeling the Effect of Audio on Human Focus in Everyday Environments Using Brain-Computer Interface Technology

Abstract: The goal of this study was to investigate the effect of audio listened to through headphones on subjectively reported human focus levels, and to identify through objective measures the properties that contribute most to increasing and decreasing focus in people within their regular, everyday environment. Participants (N = 62, 18–65 years) performed various tasks on a tablet computer while listening to either no audio (silence), popular audio playlists designed to increase focus (pre-recorded music arranged in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…They demonstrated that the effects of music reduce the subjective experience of anxiety, heart rate, and systolic blood pressure. Haruvi et al (2022) went further in their study of the positive effects of music, examining its influence on a person's level of concentration. In their study, they divided respondents into three groups and assigned several tasks on a tablet to each of them.…”
Section: Endelmentioning
confidence: 99%
“…They demonstrated that the effects of music reduce the subjective experience of anxiety, heart rate, and systolic blood pressure. Haruvi et al (2022) went further in their study of the positive effects of music, examining its influence on a person's level of concentration. In their study, they divided respondents into three groups and assigned several tasks on a tablet to each of them.…”
Section: Endelmentioning
confidence: 99%
“…Specifically, engaging these networks with high-groove rhythms may provide an efficient way to disrupt maladaptive patterns of brain activity associated with self-focused negative rumination [112][113][114] . Related to this hypothesis, there is growing evidence that groove is important for understanding effects of music on cognition, alongside affect, particularly in the context of work 110,[115][116][117][118] . For example, in one recent study, listening to a high-groove drum loop for just 3 minutes was found to be more effective than noise at improving performance on a subsequent behavioral task measuring context-dependent response inhibition (a "Stroop" test).…”
Section: Applications Of Rhythm In Mentalmentioning
confidence: 99%
“…However, the issue of mismatch between what a person likes and their treatment goals remains significant here as well. For example, listening to strongly preferred or popular music while attempting to focus tends to decrease task performance 115,117,118 , and similarly, listening to sad music when depressed can increase negative affect [248][249][250] (but see [251][252][253] ). Nevertheless, there are cases in which tailoring musical interventions to idiosyncratic preferences should be prioritized.…”
Section: Idiosyncratic Preferences?mentioning
confidence: 99%